2017
DOI: 10.1021/acsami.7b09252
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Optical Biochemical Sensors via Liquid-Cladding-Induced Modulation of Waveguide Modes

Abstract: We demonstrated modulation of the waveguide mode mismatch via liquid cladding of the controllable refractive index for label-free quantitative detection of concentration of chemical or biological substances. A multimode optical fiber with its core exposed was used as the sensor head with the suitable chemical modification of its surface. Injected analyte liquid itself formed the liquid cladding for the waveguide. We found that modulation of the concentration of analyte injected enables a degree of the waveguid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…Prior to surface functionalization with APTES/chitosan-EDTA, we measured the power transmittance response of the device, consisting of core and liquid cladding (glycerol solution, Sigma-Aldrich Co.), as we injected glycerol solutions in various concentrations. Similar to a previous report [ 24 ], we obtained a linear relationship between the glycerol concentration and the output power in a low concentration range, as shown in Figure 6 a. The mechanism of NA mismatch at the interface between the liquid cladding waveguide and the solid cladding waveguide came into play for optical power increases with increasing concentrations, as depicted in Figure 6 b. Waveguide NA = , where n core and n clad , were the indices of the core and cladding, respectively.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Prior to surface functionalization with APTES/chitosan-EDTA, we measured the power transmittance response of the device, consisting of core and liquid cladding (glycerol solution, Sigma-Aldrich Co.), as we injected glycerol solutions in various concentrations. Similar to a previous report [ 24 ], we obtained a linear relationship between the glycerol concentration and the output power in a low concentration range, as shown in Figure 6 a. The mechanism of NA mismatch at the interface between the liquid cladding waveguide and the solid cladding waveguide came into play for optical power increases with increasing concentrations, as depicted in Figure 6 b. Waveguide NA = , where n core and n clad , were the indices of the core and cladding, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Figure 2 a shows the FTIR spectrum for the silica surface of the fiber core. It was revealed that the Si-O-Si asymmetric stretching vibration mode was at 1074 cm −1 and the Si-O-Si bending vibration mode was at 456 cm −1 [ 24 , 25 ]. In addition, symmetric stretching vibration mode O-Si-O was exhibited at 821 cm −1 and 600 cm −1 [ 25 , 26 ], indicating the presence of all vibration-mode relevant silica.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations